An empirical examination of organisational culture, job stress and job satisfaction within the indirect tax administration in Malaysia - Mansor, Muzainah; Tayib, Mahamad (Center for Promoting Ideas (CPI), USA, 2010)
A study on organisational culture, employee job stress and job satisfaction within tax administrations especially in developing countries is not evidenced in the literature. This study therefore examines these aspects within the indirect tax administration in Malaysia.Data for this study was collected through a questionnaire survey on the tax employees of the Royal Malaysian Customs Wilayah Persekutuan Kuala Lumpur (RMC-WPKL). The investigation on organisational culture indicates that hierarchical culture is the dominant culture at the department.The assessment on job stress reveals that the employees are uncertain on the evaluation for a raise or promotion.The examination on job satisfaction shows that the employees are dissatisfied with the department’s concern for its employees’ welfare, and the system for recognizing and rewarding outstanding performance.It is also found that there are significant correlations among organisational culture, employee job stress and employee job satisfaction at RMC-WPKL.The results of this study signify that action should be taken to change the department’s culture orientation, reduce employees’ stress and improve employees’ satisfaction.